Saving, investment and growth: recent Asian experience - ARNDT, H.W. (PSL Quarterly Review, 2013)
Traditionally dominant economic views have been that growth is a function of investment and that investment is constrained by per capita income. The author suggests that neither assumption stands up to LDC experience. A substantial rate of investment alone does not guarantee growth, neither evidence nor common sense supports the assertion that it should. As early as the 1950s theorists posited that savings ratios depend endogenously upon growth and not vice versa. This article considers the relationships between savings, investment and growth for the Asian economies. JEL: E20